Discovery of the radio-protecting effect of Ecliptae Herba, its constituents and targeting p53-mediated apoptosis in vitro and in vivo - Jiang Wu; Wenfeng Gou; Zhiyun Wang; Huajie Chang; Deguan Li; Wenbin Hou; Changxiao Liu (Elsevier, 2023)
Radiation protection drugs are often accompanied by toxicity, even amifostine, which has been the dominant radio-protecting drug for nearly 30 years. Furthermore, there is no therapeutic drug for radiation-induced intestinal injury (RIII). This paper intends to find a safe and effective radio-protecting ingredient from natural sources. The radio-protecting effect of Ecliptae Herba (EHE) was discovered preliminarily by antioxidant experiments and the mouse survival rate after 137Cs irradiation. EHE components and blood substances in vivo were identified through UPLC‒Q-TOF. The correlation network of "natural components in EHE-constituents migrating to blood-targets-pathways" was established to predict the active components and pathways. The binding force between potential active components and targets was studied by molecular docking, and the mechanism was further analyzed by Western blotting, cellular thermal shift assay (CETSA), and ChIP. Additionally, the expression levels of Lgr5, Axin2, Ki67, lysozyme, caspase-3, caspase-8,8-OHdG, and p53 in the small intestine of mice were detected. It was found for the first time that EHE is active in radiation protection and that luteolin is the material basis of this protection. Luteolin is a promising candidate for RⅢ. Luteolin can inhibit the p53 signaling pathway and regulate the BAX/BCL2 ratio in the process of apoptosis. Luteolin could also regulate the expression of multitarget proteins related to the same cell cycle.